Spirit Budaya Islam Nusantara dalam Konstruks “Rubu’ Mujayyab - Sakirman Sakirman (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
THIS – paper examines the rubu 'mujayyab as a classical instrument and the work of ulama archipelago. Rubu 'mujayyab keeps the scientific treasures as the primary reference for the development of advanced Islamic astronomical tools. The methodology used in rubu 'mujayyab is the science of a spherical triangle connected with the concept of the earth round. Urgency rubu 'mujayyab in Islamic tradition is as a measuring tool one of them is to determine the distance and altitude. Rukyat al-hilal and the direction of Qiblah is one part that can be measured by rubu 'mujayyab. With the base of the surface point of the earth can be expressed in two coordinates, namely longitude and latitude. Through this paper submitted that rubu 'mujayyab as a measuring instrument of rukyat al-hilal and direction of Qiblah in his time is an accurate and precise tool. However, after a study with contemporary tools the calculation of rubu 'mujayyab did not reach the minute scale. In the process of calculation also requires a long process, because there are several steps that must be taken. Meanwhile, calculations using the scientific calculator method can include data processed with a formula that can produce high accuracy calculations. Yet the spirit of Islamic archipelago in the development of scientific treasures through rubu 'mujayyab still must be preserved.